2021
DOI: 10.1016/j.medj.2021.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Reduced antibody activity against SARS-CoV-2 B.1.617.2 delta virus in serum of mRNA-vaccinated individuals receiving tumor necrosis factor-α inhibitors

Abstract: Background: Although vaccines effectively prevent coronavirus disease 2019 in healthy individuals, they appear to be less immunogenic in individuals with chronic inflammatory disease (CID) or receiving chronic immunosuppression therapy. Methods: Here we assessed a cohort of 77 individuals with CID treated as monotherapy with chronic immunosuppressive drugs for antibody responses in serum against historical and variant severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) viruses after immunization with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 90 publications
7
37
0
Order By: Relevance
“…The correlation was most linear for B.1.1.529-challenged animals (R 2 = 0.8155, P < 0.0001), with a minimum neutralizing titer of approximately 2,000 required to completely prevent infection at 6 dpi. Most of the breakthrough infections occurred with the lower 0.1 μg dose of mRNA vaccines, which models what might be occurring in immunocompromised or elderly individuals, or immunocompetent individuals at times remote from completion of their primary immunization series (Chen et al, 2021a; Choi et al, 2021; Evans et al, 2021).…”
Section: Resultsmentioning
confidence: 96%
“…The correlation was most linear for B.1.1.529-challenged animals (R 2 = 0.8155, P < 0.0001), with a minimum neutralizing titer of approximately 2,000 required to completely prevent infection at 6 dpi. Most of the breakthrough infections occurred with the lower 0.1 μg dose of mRNA vaccines, which models what might be occurring in immunocompromised or elderly individuals, or immunocompetent individuals at times remote from completion of their primary immunization series (Chen et al, 2021a; Choi et al, 2021; Evans et al, 2021).…”
Section: Resultsmentioning
confidence: 96%
“…Whether the phenomenon we report is associated with protection from viruses in patients with lupus or autoimmune disease is not known ( 29 ), but this could be confounded by the immunosuppressive treatments and other factors related to these conditions. In addition to reducing immune defense, immunosuppression may also blunt COVID-19 vaccination responses ( 30 , 31 ), but our samples were collected before vaccination was available. Most studies demonstrate a similar mortality rate in SLE patients as the general population in the setting of COVID-19 ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Others have already shown that these therapies, particularly TNF inhibitors, reduce the ability of different COVID-19 vaccines (based on mRNA or Adenoviral vector) to produce Spike-specific antibodies (58) and recognize SARS-CoV-2 variants including B.1.617.2 (Delta) (4). Such results are expected, since reduced humoral responses to other vaccines (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…While these agents reduce disease burden and improve quality of life (1), they are broadly considered immunosuppressive. The COVID-19 pandemic and the necessity to implement widespread vaccination sparked debate and research on the impact of these chronic therapies on the immunogenicity of SARS-CoV-2 vaccination (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%